An Investigation of Thermodynamic Prehistory in the Formation of the Internal Structure of Highly Stable Ferroelectric Materials - Andryushin, Konstantin P.; Andryshina, Inna N.; Shilkina, Lidiya A.; Dudkina, Svetlana I.; Verbenko, Iliya A.; Reznichenko, Larisa A.; Mazuritskiy, Mihail I.; Nagaenko, Alexandr V.; Parinov, Ivan A.; Chang, Shun-Hsyung; Wang, Hung-Yu (Current Approaches in Science and Technology Research Vol. 7, 2021)
We investigated and presented our results for the dependence of the characteristics of the crystalline and grain structures of the PCR-13 material (based on the lead zirconate titanate (PZT) system), which was sintered in various ways, on the regulations for its preparation. The data from the microfluorescence analysis of the surface of ceramic materials were provided, which allowed us to state that micro X-ray fluorescence spectrometry (MICRO–XRF), supplemented by mathematical statistics, allows us to trace even small changes in the chemical composition of ceramic samples, reliably characterize the degree of surface homogeneity and provide strict mathematical conclusions related to the reproducibility of the properties of manufactured piezoelectric ceramic materials. Based on the obtained data, the optimal conditions for ceramics have been selected, which ensure homogeneity, high-density structure and reproducibility of the characteristics. This allows us to reliably use the material in frequency-selective equipment. It has been detected that the most homogeneous (perfect) structure is realized using the conventional ceramic technology.